Inhibition of Circ0001679 Alleviates Ischemia/Reperfusion-induced Brain Injury via miR-216/TLR4 Regulatory Axis - Zhang, Chenrui; Li, Liaoyu; Wang, Feng; Du, Hailong; Wang, Xiaoliang; Gu, Xiaoyu; Liu, Xinlei; Han, Haie; Wu, Jianliang; Sun, Jianping (Current Neurovascular Research, 2024)
BackgroundStroke, primarily known as ischemic stroke, is a leading cause of mortality and disability worldwide. Reperfusion after the ischemia stroke resolves is necessary for maintaining the health of brain tissues; however, it also induces inflammation and oxidative stress, resulting in brain injury. This study aimed to investigate the role of circ0001679 in the pathology of I/R (Ischemia/Reperfusion)-induced brain injury and explore its therapeutic potential for I/R injury.MethodsThe Oxygen-Glucose Deprivation/Re-oxygenation (OGD/R) model was employed in primary mouse astrocytes, and the Middle Cerebral Artery Occlusion (MCAO) model was established in mice to mimic ischemia-reperfusion-induced injury. Si-circ0001679, anti-miR-216, and TLR4 ORF-clone were transfected either in cells or mice to study the molecular mechanisms during I/R-induced injury. Inflammation and oxidative stress were monitored after treatment.ResultsUpregulated gene expression of circ0001679 was noticed in both OGD/R-treated primary mouse astrocytes and MCAO-induced mouse brain tissue. Silencing circ0001679 reduced cellular damage, inflammation, and oxidative stress induced by OGD/R treatment. Knocking down of circ0001679 alone with either miR-216 inhibition or TLR4 overexpression increased the inflammation response and oxidative stress compared to circ0001679 silencing only. Moreover, inhibition of circ0001679 attenuated brain injury in MCAO-treated mice via reduced infarction, neuronal damage, apoptosis, inflammation, and oxidative stress.ConclusionThis study unveiled a novel regulatory axis of circ0001679-miR-216-TLR4 in I/R-induced brain injury. Targeting circ0001679 may represent a promising therapeutic strategy for I/R-induced brain injury.
Keywords: miRNA